Analisis Penerapan Hukum Perdata dalam Penyelesaian Sengketa Perjanjian: Kesesuaian Penerapan Hukum dengan Prinsip Perjanjian - Br Lingga, Asma Ulhusna; Azalia, Raihanah; Novalia, Dwi; Aulia, Intan Sakinah; Harahap, Himsar Hidayat; Kurniawan, Tasya Ananda; Limbong, Agus Tagan Dera (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Agreement disputes are a phenomenon that often occurs in the practice of civil law. The application of civil law in resolving these disputes must be based on treaty principles such as pacta sunt servanda, good faith, and freedom of contract. This research analyzes the suitability of the application of civil law with these principles through a case study of a property sale and purchase contract dispute. The findings show that although the principle of pacta sunt servanda is recognized, the interpretation of good faith is often a source of disagreement. In conclusion, the application of civil law is generally in accordance with the principles of the agreement, but more consistent interpretation guidelines are needed to ensure fairness and legal certainty. Recommendations are provided to improve the understanding and application of the principles of agreement in civil law practice.